Adherence to a snacking dietary pattern is decreasing in Colombia among the youngest and the wealthiest: results of two representative national surveys - Oscar F. Herrán; Eduardo Villamor; Doris C. Quintero-Lesmes (BMC, 2019)
Abstract Background A common recommendation is to reduce the consumption of snack food and replace this consumption with nutrient-dense foods. The objective was to assess whether in Colombian children and adults there were changes in the consumption of the snack dietary pattern (SP) in the 5 years 2010-2015. In addition, this study aimed to establish the relationship between the SP and some biological, socioeconomic, and geographic variables in Colombia, South America. Methods Based on a Food Frequency Questionnaire (FFQ) applied both in 2010 and 2015 in the national nutritional situation surveys, the adherence to the snack consumption pattern was established through factor analysis. The change in the adherence of consumption to the SP was established for the five-year period [2015 minus 2010], using multiple linear regression models. Crude and adjusted differences were estimated by the following covariables: sex, age, marital status, food security, wealth index, ethnicity, education of the head of the household, area and region. In total, 37,981 subjects were analyzed. In 2010, 10,150 children (5 to 17 years old) and 5145 adults (18 to 64 years old) were included, and in 2015, 13,243 children and 9443 adults. Results In children, the adjusted difference in the adherence to SP was − 0.37 (95% CI: − 0.42, − 0.32). In adults, the adjusted difference in the adherence to SP was − 0.27 (95% CI: − 0.31, − 0.24). In all categories of covariables, consumption decreased, for all p < 0.0001. In children, the decrease in consumption was inversely associated with height-age. The decrease was smaller at the extremes of the BMI distribution, Z < -2 and Z > 2. The decrease in consumption was directly associated with the level of food security in the home and the wealth index. In adults, the decrease in consumption was inversely related to age and was directly related to the level of food security of the household, wealth index, and education level. The BMI decrease was greater in subjects with 18.5-24.9. In subjects with 30+, it was lower than in subjects with 25.0-29.9. Conclusions In the 5 years 2010-2015, snack consumption is decreasing. The region, the richest subjects, those with adequate BMI, and in households with more educated heads of household, achieved a greater decrease in SP.